Laughing skull - Bond, Ruskin (New Delhi Rupa publications, 2016)
In the middle of the night, I woke to a loud rattling sound. A rat, perhaps? But no. As soon as I opened the cupboard door, out popped the skull$1 (Blanding near my feet and bouncing away right across the drawing room.Ghosts and spirits, prets and jinns abound in this collection of stories. From the skull that refused to be given away to the spirits of long dead hill-station residents and from the mysterious man you meet on a dark road to the malevolent presence at the bottom of a pond$1 (Bthese are some of Ruskin Bond$1 (Bs best stories about the supernatural. Dive under the covers, leave the lights on and lose yourself in these scary, funny and adventurous tales.s
Keywords: Fiction